Appreciative inquiry: a constructive approach to organization development and change - Cooperrider, David L. (New York: David L.C. and Associates, 1996)
This handbook is an invitation to an imaginative and fresh perception of organizations and the process through which they change. Its meta-cognitive stances is Choicefutty affirmative. And its central thesis-as an extension of the lewinian premise that human action is dependent on the world as constructed rather then the world as it is-is pragmatic an hopeful.
Commentary at the end of the Cach Chapter
Keywords: Mercadeo; Relaciones Públicas